Street food environmental sustainability in a urbanizing global south: A social practice perspective - Vignola, Raffaele; Oosterveer, Peter (Frontiers Media, 2022)
Selling and buying street food is an every-day practice for millions of urban poor living in cities across Africa, Asia, and Latin America. These practices are embedded in social routines (e.g., for producing food to consuming it and disposing waste) that are dependent on and influence the environmental performance of urban food systems as agents make use of resources (e.g., soil, water, energy, ingredients, etc.). A social science theory being increasingly applied to food systems and sustainability transformations, social practice theory focuses attention on the cultural, institutional, and physical embeddedness of social routines that characterize street food systems. It allows identifying barriers and lock-ins as well as opportunities to de-routinize unsustainable practices and help visualize the linkages and opportunities to nudge the routinization of sustainable practices. Through three examples of social practices in street food systems of the global south, we illustrate those linkages and propose a research agenda to step up the use of these perspective in promoting the contribution of urban street food system to sustainability.